Museums and Cultural Representations of Disability: between individual identity and collective history (Cadernos de Sociomuseologia, 2024)
This chapter explores some concerns and values that are part of the reflective processes that led me to the construction of scientific knowledge in museology, raising questions about the very nature of the cultural meaning of disability. It also introduces theoretical and practical issues surrounding the representation of disability, challenging the relationship between museums and disability as spaces of exclusion/inclusion, of cultural meaning-making, but also of the perpetuation of discriminatory practices and stereotyping. Thus, while speaking from the perspective of my experience as a researcher in the field of museology and disability studies, I will take this opportunity to reflect on my own biography, taking the risk, perhaps, of venturing down more uncertain paths, but ones that have guided and shaped my professional journey in thinking and conducting research on museums and disability.The motivations for doing so are varied. On the one hand, I am interested in exploring the relationship between the researcher’s biography and the production of scientific knowledge developed within academia—mediating relationships between people, between people and things, and between people and both the physical and imaginary worlds. On the other hand, I am interested in materializing a narrative that intertwines and overlaps identity issues with the object of study. Moreover, reflecting on my own biography allows me to explore issues of representation in a cross-cutting manner, understanding perspectives that encompass different views on how the cultural meaning of disability impacts relationships between disabled and non-disabled people, but above all, on the identity construction of our own selves and conventional notions of otherness.Keywords: Keywords: Disability. Representation. Museums. Identity. Museum Speeches. Social inclusion.